2020
DOI: 10.1146/annurev-matsci-090519-113456
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Two-Dimensional Layered Transition Metal Dichalcogenides

Abstract: Transition metal dichalcogenide (TMD) monolayers and heterostructures have emerged as a compelling class of materials with transformative properties that may be harnessed for novel device technologies. These materials are commonly fabricated by exfoliation of flakes from bulk crystals, but wafer-scale epitaxy of single-crystal films is required to advance the field. This article reviews the fundamental aspects of epitaxial growth of van der Waals–bonded crystals specific to TMD films. The structural a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 110 publications
1
55
0
Order By: Relevance
“…Also, the precursor sources and some gaseous by‐products (e.g., CO) are toxic, thus precautions need to be implemented to deal with the toxic gases in the MOCVD growth of TMDCs. [ 85 ] The growth of other 2D vdW materials (MXene, BP, and Te, MoO 3 ) has not been reported by MOCVD yet.…”
Section: Wafer‐scale Growth Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the precursor sources and some gaseous by‐products (e.g., CO) are toxic, thus precautions need to be implemented to deal with the toxic gases in the MOCVD growth of TMDCs. [ 85 ] The growth of other 2D vdW materials (MXene, BP, and Te, MoO 3 ) has not been reported by MOCVD yet.…”
Section: Wafer‐scale Growth Methodsmentioning
confidence: 99%
“…However, some precursors may cause possible carbon residuals contamination in the grown 2D film. [56,85] In contrast to TMDCs, few studies were reported on the growth of graphene and h-BN by the MOCVD process. [86][87][88] Examples of MOCVD processes used to grow TMDCs are illustrated in Figure 11b-f.…”
Section: Mocvd Growth Processmentioning
confidence: 99%
“…Typically, MOCVD requires lattice‐matched substrates, such as sapphire and GaN, for growing epitaxially aligned 2D TMDs. [ 51,56 ] It can grow good TMDs on vdW substrates, such as graphene, boron nitride, and TMDs by vdW epitaxy at high temperature (≥ 800 °C). [ 57 ]…”
Section: Thin‐film Techniques For the Compositional Engineering Of 2d Tmdsmentioning
confidence: 99%
“…Si maybe is not the best candidate for growth of 2D TMCs, due to the symmetry not matching well. [197,269] The TMCs do not grow readily on Si in general. [270] Will other substrates like GaN, 4H-or 6H-SiC be good candidates for wafer-scale growth?…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%